Studi Pendahuluan Pemanfaatan Sludge IPAL Industri Tekstil Sebagai Bahan Baku Briket: Study of Utilization Textile Industry Sludge from WWTP as Raw Material for Briquettes - RAHMAULINA, DINI; HARTATI, ETIH; MARGANINGRUM, DYAH (Jurnal Teknologi Lingkungan, 2022)
ABSTRACT The sludge textile industry was a by-product from wastewater treatment plant (WWTP) categorized as toxic and hazardous waste, sludge (SL) produced every day from WWTP could cause problems in the factory environment, such as reducing the storage space and aesthetic of the factory environment. This study discussed sludge that will be used as raw materials for briquettes. The analysis of the study was based on proximate analysis, calorific value, total sulfur, heavy metals, and slagging and fouling potential, which used method ASTM, AAS, Spectrophotometry and Gravimetry. These sludge briquettes materials were also added with additional raw material: bottom ash (BA); afterwards, it was mixed with sludge, and the compositions were 90%BA:10%SL, 80%BA:20%SL, and 70%BA:30%SL. The characteristic quality of briquettes was compared to Ministry of Environmental Regulation Number 06 of 2021 and Indonesia National Standard Number 4931 of 2010. The analysis of sludge material for briquette had moisture content, ash content, volatile matter, fixed carbon, calorific value, and total sulfur of 2.57%, 7.92%, 4.76%, 13.47%, 1,172 kcal/kg, and 0.98%, respectively. In addition, the slagging and fouling potential indicated moderate and low classification with the impact value index of 0.310 and 0.412, respectively. The study results also showed that the best briquette was a briquette that uses a composition of 70%BA:30%SL. This briquette had a calorific value of 1,473 kcal/kg; however, it has not met the provisions of the Ministry of Environmental and Forestry Regulation Number 06 of 2021 and Indonesia National Standard Number 4931 of 2010.   ABSTRAK Sludge Industri Tekstil merupakan hasil samping dari proses Instalasi Pengolahan Air Limbah (IPAL) yang tergolong ke dalam limbah B3, sludge (SL) yang dihasilkan dari IPAL dapat menimbulkan masalah berupa berkurangnya ruang penyimpanan sludge serta menganggu estetika lingkungan pabrik. Studi ini membahas sludge yang selanjutnya akan digunakan sebagai bahan baku bahan bakar briket. Analisis studi yang akan dikaji yaitu analisis proksimat, nilai kalor, total sulfur, kandungan logam berat serta potensi terjadinya slagging dan fouling menggunakan metode ASTM, AAS, Spektrofotometri serta Gravimetri. Briket berbahan baku sludge kemudian ditambahkan bahan baku tambahan berupa bottom ash (BA) yang kemudian dicampur dengan sludge pada komposisi 90%BA:10%SL, 80%BA:20%SL, dan 70%BA:30%SL. Kualitas briket tersebut dibandingkan dengan Peraturan Menteri Lingkungan Hidup No 06 Tahun 2021 dan SNI 4931 Tahun 2010. Berdasarkan studi yang dilakukan sludge memiliki kandungan kadar air, kadar abu, volatile matter, fixed carbon, nilai kalor, dan total sulfur secara berturut-turut 2,57%, 79,2%, 4,76%, 13,47%, 1.172 kkal/kg dan 0,98%. Selain itu penggunaan sludge terhadap potensi slagging dan fouling terindikasi sedang dan rendah dengan indeks secara berturut-turut 0,310 dan 0,412. Berdasarkan studi, briket terbaik terdapat pada briket dengan komposisi 70%BA:30%SL dengan nilai kalor sebesar 1.473 kkal/kg namun briket tersebut masih belum memenuhi kualitas yang diharapkan berdasarkan Peraturan Menteri Lingkungan Hidup dan Kehutanan Nomor 06 Tahun 2021 dan SNI 4931 Tahun 2010.